Development of Chemistry in Context E-book on Chemistry Subject Grade XI of Senior High School for Facing Literacy and Numerical Competency Assessment - Salsabila, Elfina; Sari, Rr. Lis Permana (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
This research aimed to develop an e-book titled